1996
DOI: 10.1007/bf02358611
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion on hydrophilic heparinized catheters, with compared with adhesion on silicone catheters, in patients with malignant obstructive jaundice

Abstract: To study the inhibitory effects on bacterial adhesion of a newly devised, hydrophilic heparinized catheter to be used in patients with malignant obstructive jaundice, a randomized controlled study of indwelling endoprostheses was performed, using implantable port-connected heparinized catheters (n = 25) and silicone catheters (n = 21). Catheters withdrawn from patients were cultured for bacteria and examined by electron microscopy for the presence of adherent organisms. In vitro examination of the two type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Frequently, an ERCP is performed with placement of endoprosthesis to stent localized strictures and facilitates pancreatic drainage. These catheters commonly become obstructed due to sludge adhesion with subsequent aerobic and anaerobic bacterial overgrowth [21,22] . Several studies have examined the microbial fl ora of biliary stents after removal and it has been shown that bacteria can be isolated from the majority of these endoprosthesis [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, an ERCP is performed with placement of endoprosthesis to stent localized strictures and facilitates pancreatic drainage. These catheters commonly become obstructed due to sludge adhesion with subsequent aerobic and anaerobic bacterial overgrowth [21,22] . Several studies have examined the microbial fl ora of biliary stents after removal and it has been shown that bacteria can be isolated from the majority of these endoprosthesis [23,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have demonstrated that the use of negatively charged materials, such as ionized plastics, Teflon, or heparinized surfaces, is of particular benefit in reducing colonization (2,11,12,15). Moreover, since the teichoic acid content and the degree of D-alanylation vary among S. aureus strains (16), increased amounts of D-alanine esters may contribute to the capacity of staphylococci to colonize indwelling devices.…”
Section: Fig 1 Biofilm Formation By S Aureus Strains In Polystyrenmentioning
confidence: 99%
“…31,32 However, we produced a biliary endoprosthesis in which an H-PSD tube was connected with the implanted port, 16 which enabled us to easily resolve jaundice and thus appeared to contribute to the increase of the survival rate. 31,32 However, we produced a biliary endoprosthesis in which an H-PSD tube was connected with the implanted port, 16 which enabled us to easily resolve jaundice and thus appeared to contribute to the increase of the survival rate.…”
Section: Discussionmentioning
confidence: 99%